A boundary-based approach to the multiscale microstructural characterization of a W-Ni-Fe tungsten heavy alloy. (May 2022) - Haag, J.V.; Wang, J.; Edwards, D.J.; Setyawan, W.; Murayama, M.
Abstract: A combination electron backscattered diffraction and transmission electron microscopy based approach has been implemented to study the effects of purposefully introduced anisotropy in a tungsten heavy alloy (WHA) through hot-rolling. Particular attention has been paid to changes in number and proportion of various boundary types from a quantitative standpoint; incorporating qualitative behavioral observations from prior analyses to generate experimentally-validated bases for the examination and application of a microstructure which exhibits an optimal balance of strength and ductility. It is asserted that a combination of increased temperatures during rolling and additional isothermal hold time for the post-rolling annealing steps may lead to a reduction in unfavorable textural components due to rolling in the W-phase and a decrease in premature fracture due to W-W microcracking respectively. This is expected to further increase the proportion of interphase boundaries and improve the ductility of these rolled structures, producing a superior rolled WHA microstructure. Graphical abstract: Image, graphical abstract